Characterization of conduction band edge discontinuity for InAlAs/GaAsSb using InP/GaAsSb heterojunction bipolar transistors - Ng, C. W. (2013)
In this work, the temperature-dependent DC performance of InP/GaAsSb double heterojunction bipolar transistors (DHBTs) with an InP/InAlAs composite emitter was characterized. The current transport mechanisms in DHBTs with a type-I InAlAs/GaAsSb emitter–base junction interface and a type-II GaAsSb/InP base–collector were studied. The experimental results reveal that electron injection at emitter–base junction could be affected by conduction barrier limited carrier transport. A conduction band edge discontinuity of 9.5 meV for InAlAs/GaAsSb heterojunction was experimentally estimated.